Optimalisasi Transformasi Kesadaran Lingkungan Masyarakat melalui Edukasi Visual dan Penguatan Praktik Pengelolaan Sampah Berkelanjutan - Listari, Putri Amanda; Kamil, Ahmad Zaidanil; Nur’aini, Putri Nabila; Nashirulloh, Ismail Yahya; Frianoka, Mardela Yuwan; Ramadhan, Muhammad Andi; Islamiah, Rahmatul; Aqila, Nada; Astine, Adellia Juni (Forum Kerjasama Pendidikan Tinggi, 2026)
The issue of waste management remains a major challage at the rural level, especially in areas that do not yet have supporting infrastructure such as a final Disposal Site (TPA). Tarokan Village, Banyuanyar Sub-district, Probolinggo Regency, East Java, is one of the areas facing this problem. The community tends to dispose of waste into ravines and rivers, leading to environmental pollution, ecosystem damage, and health risks for residents. This community service program aims to improve the understanding and skills of Tarokan Village residents in sustainable waste management through a Participatory Action Research (PAR) approach. The activities' methods included observing the waste disposal conditions, designing and installing visual educational signs at strategic points, and interactive socialization involving women cadres, village officials, and public health center (Puskesmas) health workers. The implementation results showed a significant increase in community participation, reflected by the attendance of 65% of participants from the total invitations and high enthusiasm during the activities. Visual education played an effective role in building ecological awareness and encouraging changes in community behavior. Furthermore, the program successfully triggered follow-up initiatives such as the plan to establish a Village Waste Bank as an effort for the activity's sustainability. The visual and participatory-based education model implemented proved relevant to be replicated in other areas with similar conditions, while also contributing to the achievement of Sustainable Development Goals (SDGs) points 11 and 12, which emphasize the importance of sustainable settlements and responsible consumption.